Collaborative multiview time series modeling for vehicle maintenance demand prediction - Fanghua Chen; Deguang Shang; Gang Zhou; Ke Ye; Fujie Ren; Guofang Wu (Scientific Reports)
Abstract Accurate prediction of vehicle maintenance demands is crucial for sustaining vehicle use, optimizing performance, and minimizing ownership costs. However, current methods only predict maintenance demand for specific vehicle components and lack the capability to offer a comprehensive prediction of all maintenance demands. Furthermore, predicting vehicle maintenance demand must incorporate the impacts of various essential maintenance projects on subsequent demands. To address these challenges, we propose an innovative method for predicting vehicle all maintenance demands based on collaborative multiview time series modeling. Leveraging the interdependencies among vehicle maintenance projects across various time periods, we employ a temporal dependency learning approach utilizing a multi-attention mechanism. To enhance the interaction between distinct time points and temporal dependencies, we developed a dependency-aware learning algorithm that effectively integrates and weighs the information and dependencies at each time step, thereby improving the model’s ability to capture the complex relationships among maintenance projects over time. To capture the significant impact of key maintenance projects on future demands, we propose a module that leverages both long short-term memory networks and the attention mechanism. Experimental results on actual vehicle maintenance records confirm that the proposed model outperforms existing methods, demonstrating its efficacy and applicability in predicting vehicle maintenance demand.